AI powered social commerce technology and customer experience: A systematic literature review - Akinola, P. O.; Bilro, R. G.; Loureiro, S. M. C. (15th Annual Conference of the EuroMed Academy of Business: Sustainable Business Concepts and Practices, 2022)
Over the last 3 decades, the digital revolution has drastically transformed customer/user experience. Negroponte (1995) described this transformation as a shift from atoms to bits. Schmitt (2019) supported that, in the context of marketing atoms are fast moving consumer goods and their brands, made in factories, advertised through mass media, and sold in stores; bits are information, entertainment and interactive products, often produced instantaneously, promoted through social media and sold online. Artificial Intelligence (AI) powered technologies such as social commerce, Internet of things (IoT), Augmented reality (AR), Virtual Reality (VR), Smart technology, or digital payments technologies have the potential to revolutionize customer or user experience. Artificial intelligence (AI) is reshaping business, economy, and society by transforming consumers experiences and relationships amongst stakeholders and citizens (Loureiro, Guerreiro and Tussyadiah, 2020).